2009
DOI: 10.1111/j.1447-0594.2009.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial trauma in geriatric patients in a selected Malaysian hospital

Abstract: All the elderly patients with facial trauma were managed conservatively or as closed reduction in this hospital. This was largely because of their comorbid state and financial constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 13 publications
5
23
2
1
Order By: Relevance
“…7 Although fracture location in geriatric patients is certainly influenced by mechanism of injury, [28][29][30] our data indicate that mechanism of injury did not completely explain fracture location. 4 Rather, organic skeletal and biological differences, 31 such as osteoporosis and posterior edentulism, in geriatric patients are likely to account for these differences in fracture location.…”
Section: Discussionmentioning
confidence: 83%
“…7 Although fracture location in geriatric patients is certainly influenced by mechanism of injury, [28][29][30] our data indicate that mechanism of injury did not completely explain fracture location. 4 Rather, organic skeletal and biological differences, 31 such as osteoporosis and posterior edentulism, in geriatric patients are likely to account for these differences in fracture location.…”
Section: Discussionmentioning
confidence: 83%
“…This feature is similar to that in other studies in Japan, 3,7 although it is in contrast to studies in other countries which reported a male majority. 8,9 The reason for this discrepancy may be that the average longevity of females is higher than that of males in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…La proporción entre el sexo masculino y femenino de 2,9:1 (pre-GES) y 2,5:1 (post-GES) (Fig. 1) fue similar a la observada en otros estudios (Abdul Rahman et al, 2010;Acevedo et al;Locker, 2007).…”
Section: Discussionunclassified